(untitled) (World Economics and Finance Bulletin, 2026)
Nowadays, the activities of non-state non-profit organizations (NSNPOs) s in Uzbekistan are primarily aimed at alleviating the social costs of implementing the reform program by creating conditions for protecting the poor, elderly and disabled members of society, expanding employment and professional reorientation of the population, promoting reforms in rural areas and small towns, stimulating development of small and medium-sized businesses. Therefore, this article discusses the solution to the problems of remuneration audit in non-state non-profit organizations (NSNPOs) in Uzbekistan. And also, the procedure for auditing the accounting of labor remuneration in non-governmental non-profit organizations is recommended.